Legume-based crop rotation sustain the soil biodiversity, fertility levels, productivity, and profitability: evidence from a long-term study under Indian subtropical conditions - Walia, Sohan Singh; Rani, Neeraj; Ravisankar, Natesan; Bhagat, Rakshit; Kaur, Tamanpreet; Kaur, Karmjeet (Frontiers in Agronomy, 2025)
Prolonged cultivation of the rice–wheat system in the Indo-Gangetic Plain (IGP) has led to soil degradation, groundwater depletion, and reduced input use efficiency, necessitating resilient and diversified cropping systems. Therefore, a 6-year field experiment (from 2017–2018 to 2022–2023) was conducted at Punjab Agricultural University (PAU), Ludhiana, Punjab, India, using a randomized complete block design with four replications to evaluate 10 cropping systems (CS). The results revealed that the legume-integrated cropping system of maize–peas–spring groundnut (CS6), being statistically at par with other legume-based systems (i.e., CS3, CS4, CS5, and CS8), showed a significantly lower bulk density (1.32 g/cm3) and higher availability of macronutrients [nitrogen (250.88 kg/ha), phosphorus (27.87 kg/ha), and potassium (194.12 kg/ha)] and micronutrients [zinc (2.85 mg/kg), iron (25.02 mg/kg), copper (2.67 mg/kg), and manganese (12.35 mg/kg)], as well as a substantially improved soil biological health, as indicated by the increased microbial populations [bacteria (132.56 × 106 CFU/g), fungi (25.34 × 103 CFU/g), actinomycetes (35.01 × 104 CFU/g), and diazotrophs (97.32 × 104 CFU/g)], enzymatic activity [dehydrogenase (62.22 µg TPF/g soil/h), alkaline phosphatase (10.78 µg PNP/g soil/h), and urease (16.96 µ/g soil/h)], and microbial biomass carbon (255.21 mg/kg) and nitrogen (20.01 mg/kg). The correlation analysis showed significant interrelationships (p ≤ 0.01 and 0.05), while the principal component analysis (PCA) identified the legume-based systems as key contributors to improved soil health. The cropping system CS6 produced 68.97% higher rice equivalent yield (199.88 q/ha) than the rice–wheat system (118.29 q/ha), consequently resulting in higher gross returns (₹391,770/ha), net returns (₹233,193/ha), benefit/cost (BC) ratio (1.47), and economic efficiency (₹639/ha/day), making it the most economically and ecologically sustainable system recommended for adoption.